Respuesta :

First, we just need y and not 3y. So, we divide both sides by 3.

y = -3x + 2

This equation is shown as y = mx + y-intercept, m being the gradient or slope so -3 is the slope.

Answer:

  • The slope is -3.

Step-by-step explanation:

Let's simplify the equation.

We know that:

  • Formula = y = mx + b
  • m = slope
  • b = y-intercept

Work:

  • 3y = -9x + 6
  • => y = -9x/3 + 6/3
  • => y = -3x + 2

Let's compare the formula with our resulting equation.

  • => (y = -3x + 2) = (y = mx + b)
  • => -3x = mx
  • => -3 = m

Hence, the slope is -3.

Hoped this helped.

[tex]BrainiacUser1357[/tex]

Ver imagen Аноним
ACCESS MORE